Desafio: transformar Gonçalves (MG) em uma cidade conectada - Alexandri, Adrian de (2018)
In the digital age, journalism allows the citizen to appropriate numerical tools and be a news producer, socially and economically impacting the place where he lives. Thus, participatory and hyperlocal journalism, with the use of georeferencing technologies, are being applied in a rural region of Brazil - Gonçalves (MG). From bibliographic research, field research and interviews, a website was created and implemented in the city. A public agenda is thus revealed and, supported by these tools, can achieve benefits for the society of its surroundings to the point that, starting from the connection, start a process with parameters of smart city.